PENGARUH PEMAHAMAN MERDEKA MENGAJAR, MOTIVASI KERJA DAN SARANA PRASARANA TERHADAP KESIAPAN MENGAJAR GURU SMKN PROGRAM KEAHLIAN TEKNIK KOMPUTER DAN JARINGAN - Nurul Sakinah; Jaya, Hendra; Arfandi, Anas (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2026)
This study aims to determine the effect of understanding independent teaching on teacher teaching readiness, the effect of work motivation on teacher teaching readiness, the effect of facilities and infrastructure on teacher teaching readiness and the effect of understanding teaching, work motivation and facilities and infrastructure on teacher teaching readiness together. This research is a type of quantitative research with a survey approach. This study because the population is not more than 100 respondents, the researcher took 100% of the population in the data of productive TKJ SMKN Makassar City teachers, which is 19 respondents. Data collection uses observation, documentation and questionnaires. Data analysis techniques use descriptive statistics and inferential statistics. The prerequisite test uses the normality test, linearity test, multicollinearity test and heteroscedasticity test. The results of the descriptive analysis show that Understanding Independent Teaching, Work Motivation, Facilities and Infrastructure and Teacher Teaching Readiness of SMKN Makassar City have high criteria. Hypothesis testing uses simple linear regression and multiple linear regression tests. The results of this study indicate that (1) There is an influence of understanding independent teaching on the teaching readiness of TKJ teachers at SMKN Makassar City. (2) There is an influence of work motivation on the teaching readiness of TKJ teachers at SMKN Makassar City. (3) There is an influence of facilities and infrastructure on the teaching readiness of TKJ teachers at SMKN Makassar City. (4) There is an influence between understanding independent teaching, work motivation and facilities and infrastructure on the teaching readiness of TKJ teachers at SMKN Makassar City. So that the research hypothesis is accepted.